Oceanic Mesoscale Eddy Depletion Catalyzed by Internal Waves. Issue 18 (22nd September 2021) - Barkan, Roy; Srinivasan, Kaushik; Yang, Luwei; McWilliams, James C.; Gula, Jonathan; Vic, Clément
Abstract: The processes leading to the depletion of oceanic mesoscale kinetic energy (KE) and the energization of near‐inertial internal waves are investigated using a suite of realistically forced regional ocean simulations. By carefully modifying the forcing fields we show that solutions where internal waves are forced have ∼ 25 % less mesoscale KE compared with solutions where they are not. We apply a coarse‐graining method to quantify the KE fluxes across time scales and demonstrate that the decrease in mesoscale KE is associated with an internal wave‐induced reduction of the inverse energy cascade and an enhancement of the forward energy cascade from sub‐to super‐inertial frequencies. The integrated KE forward transfer rate in the upper ocean is equivalent to half and a quarter of the regionally averaged near‐inertial wind work in winter and summer, respectively, with the strongest fluxes localized at surface submesoscale fronts and filaments. Plain Language Summary: Oceanic eddies contain most of the kinetic energy in the ocean and therefore play an important role in determining the ocean's response to future climate scenarios. Oceanic wind‐ and tidally forced internal waves are energetic fast motions that contribute substantially to the vertical mixing of water, thereby affecting biogeochemical and climate processes. This work shows for the first time in high‐resolution, realistically forced, numerical simulations that wave motions can drain a substantial amount of eddy energy by altering the way in which energy is transferred across scales. This has important implications to ocean energetics and to climate models that often lack the resolution and forcing components to represent these wave‐induced effects. Key Points: Wind forced near‐inertial waves and internal tides can efficiently drain oceanic mesoscale eddy energy Eddy energy "draining" is largely a result of an internal‐wave induced modifications to the turbulent energy cascades The strongest forward energy transfers are found in submesoscale fronts and filaments that dynamically depart from geostrophic balance